Non-contact gas turbine blade vibration measurment from casing pressure and vibration signals - A review - Forbes, Gareth; Randall, R. (TBA, 2010)
This paper presents a summary of a recent research program, focusing on a new method of non contact gas turbine blade vibration measurement using casing pressure and vibration signals. Currently the dominant method of non contact measurement of turbine blade vibrations employs the use of a number of proximity probes located around the engine periphery measuring the blade tip (arrival) time (BTT). Despite the increasing ability of this method there still exist some limitations, viz: the requirement of a large number of sensors for each engine stage, difficulties in dealing with multiple excitation frequencies, sensors being located in the gas path, and the inability to directly measure the natural frequency of a given blade. Simulations established with a physics based model along with experimental measurements are presented in this paper, using internal pressure and casing vibration measurements, which have the potential to rectify some of these problems.